2021
DOI: 10.3390/ijerph18136800
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Unintentional Injuries among In-School Adolescents in Ghana

Abstract: Injuries among adolescents pose significant public health problems. Unintentional injuries are the leading cause of adolescents’ mortality and disability with the largest burden in low-and middle-income countries. Yet, there is paucity of data in Ghana on adolescent injuries. The present study aimed to determine the prevalence and correlates of unintentional injuries among in-school adolescents in Ghana using data from the Global School-Based Health Survey. Cross-sectional data on 2058 adolescents in junior an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 35 publications
6
10
1
Order By: Relevance
“…Adolescents who engaged in a physical fight had a higher tendency of experiencing serious injuries than those who never engaged in a fight. The current finding supports previous studies [ 20 , 23 ]. Perhaps, the strong association between indulging in aggressive behaviors such as engaging in physical fights and injury sustenance could account for this noted finding [ 23 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Adolescents who engaged in a physical fight had a higher tendency of experiencing serious injuries than those who never engaged in a fight. The current finding supports previous studies [ 20 , 23 ]. Perhaps, the strong association between indulging in aggressive behaviors such as engaging in physical fights and injury sustenance could account for this noted finding [ 23 ].…”
Section: Discussionsupporting
confidence: 94%
“…Corroborating the findings of previous studies [ 17 , 20 , 23 ], the study found that adolescents who experienced bullying were more likely to experience serious injuries than those who were never bullied. From the frustration-aggression perspective, adolescents who are bullied are more likely to retaliate violent behaviors perpetrated against them, causing them to be physically attacked which subsequently increases their probability of sustaining injuries [ 23 25 ].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The present study found that injury contributed to the increased likelihood of high psychological distress including suicidal behavior among young people. Injury may have poorly affected the physical and psychological health of adolescents, making them vulnerable to mental distress [ 41 ].…”
Section: Discussionmentioning
confidence: 99%